Uso de estrategias de producción de textos en inglés en estudiantes de segundo grado de secundaria en instituciones educativas públicas y privadas del distrito de Iquitos 2022 - Paima Lopez, Marco Antonio (2025)
The study conducted in 2022 analyzed the use of strategies for English text production among second-year high school students from public and private institutions in Iquitos. Of a comparative type and field design, contemporary cross sectional and univariate, it included a sample of 330 students and 62 English teachers. The results revealed differences in the perceptions of both groups. The students did not identify significant differences in planning (p = 0.311), feedback (p = 0.073), and publication (p = 0.348), while the teachers did perceive significant variations (p < 0.05). Regarding the use of strategies, students consider that in public institutions they are not regular (X̅ = 58.869) and in private ones they are not adequate (X̅ = 53.683), while teachers rate them as regular in public institutions (X̅ = 65.07) and adequate in private ones (X̅ = 86.95). In editing strategies, both groups agree that there are significant differences in their application (p < 0.05). Finally, the null hypothesis was accepted for students (p = 0.060 > 0.05), indicating that there are no differences in their use, while for teachers the alternative hypothesis was accepted (p = 0.001 < 0.05), showing significant differences in their application.